Purification of the textile finishing effluents by the ultrafiltration technique - Berradi, Mohamed; El Harfi, Ahmed (International Journal of Advanced Chemistry, 2014)
In the present paper, we synthesized, at first, an new permeable organic membrane based on a mixture of different percentages of pol-ysulfone (PSU), 4,4-sulfoxylphenol S, expanded polystyrene in a solvent that is N, N-dimethylformamide (DMF), and at the end, we treated the liquid effluents from the textile finishing industry by this membrane. The latter was characterized at the first step by the hydrodynamic conditions of the ultrafiltration technique and in a second step by microscopic tools. The achieved results concerning the microscopic characterization of the synthesized membrane show that the chemical structure of the membrane is composed of three previous components (PSU/BS/PSe), but those related to wastewater treatment show that the rate of discoloration measured for the wastewater charged with indigo is the order of 87.24% and measured for the black sulphur is the order of 64.04%.   Keywords: Permeable Organic Membrane, Ultrafiltration, Hydrodynamic and Microscopic Characterization.